A consideration of polychlorinated biphenyls as a chemostratigraphic marker of the Anthropocene. (August 2020) - Gałuszka, Agnieszka; Migaszewski, Zdzisław M; Rose, Neil L
Polychlorinated biphenyls, organic pollutants of anthropogenic origin, were widely used in many industrial applications worldwide roughly from the 1930s to the 1970s. Both the use and disposal of polychlorinated biphenyls contributed to their ubiquity in different environmental compartments, and they show extremely high persistence because of their high physical and chemical stability. Concentrations of polychlorinated biphenyls in environmental archives located in different parts of the world usually show an initial increase in the 1940s–1950s and maxima in the 1960s–1970s followed by a sharp decline following the ban in their use. Thus, the increase in polychlorinated biphenyl concentrations would appear to be suitable as a chronostratigraphic marker in Anthropocene strata. This manuscript discusses the polychlorinated biphenyls record in different environmental archives in the context of temporal and spatial trends in production and application of these compounds as well as the advantages and disadvantages of the use of polychlorinated biphenyls in the chemostratigraphy of the Anthropocene series.